Identification of Two Distinct Sites for Antagonist and Biased Agonist Binding to the Human Chemokine Receptor CXCR3 - Milanos, Lampros; Saleh, Noureldin; Kling, Ralf; Kaindl, Jonas; Tschammer, Nuska; Clark, Timothy (Angewandte Chemie International Edition, 2016)
The chemokine receptor CXCR3 is a G protein-coupled receptor that conveys extracellular signals into cells by changing its conformation upon ligand binding. We previously hypothesized that small-molecule allosteric CXCR3-agonists do not bind to the same allosteric binding pocket as 8-azaquinazolinone-based negative allosteric modulators. We have now performed molecular-dynamics (MD) simulations with metadynamics enhanced sampling on the CXCR3 system to refine structures and binding modes and to predict the CXCR3-binding affinities of the biased allosteric agonist FAUC1036 and the negative allosteric modulator RAMX3. We have identified two distinct binding sites; a shallow and a second deeper pocket to which the biased allosteric agonist FAUC1036 and negative allosteric modulator RAMX3 bind, respectively.
Keywords: allosterism; membrane proteins; molecular dynamics; protein structures; signal transduction